Awareness about cervical cancer screening among reproductive aged women attending gynaecology outpatient department in ESI PGIMSR & ESIC medical college & Hospital, Joka, Kolkata - Chaudhuri, Susmita; Dutt, Rekha; Goswami, Shweta; Roychowdhury, Joydeb (International Journal Of Community Medicine And Public Health, 2017)
Background: Cervical cancer is a leading cause of morbidity and mortality in women especially India. The mainstay of prevention rests on early detection of cases through screening. So, this study aims to determine the knowledge of cervical cancer screening, Human papilloma virus & its vaccination status. Methods: This was an observational study of cross-sectional design conducted among the adult reproductive aged women (18-45 years) visiting Gynaecology OPD at ESI-PGIMSR and ESIC Medical College and Hospital, Joka. A pre-designed and pre-tested interview schedule was prepared. Face to face interview was conducted in local language. Data was compiled & computed in SPSS software version 20. Results: Total respondents were 97. Majority of the respondents (62.9%) belong to the age group of 21-30 years. 8 in 10 participants follow Hinduism. Almost equal percentages of participants were from urban & rural areas (51.5% & 48.5% respectively). 6 in 10 participants had heard about cervical cancer. Majority of the respondents (55%) mentioned friends & family as a source of information. 48.3% of the respondents knew poor genital hygiene as a predisposing risk factor for cervical cancer. Very few knew about other factors like multiple sexual partner (20%), early marriage (33.3%), young age (20%), repeated childbirth (35%), OCP usage (26.7%) as risk factors for cervical cancer. Only one participant had undergone screening test for cervical cancer (1.7%). 46.7% of the respondents were aware about association of HPV infection with cervical cancer. But none of the participants had received vaccine against cervical cancer & they cited lack of awareness as a reason for not receiving the vaccine. Conclusions: A well-designed health education program focusing on effective multipronged IEC strategies utilizing pictorials, audio-visual and personal communication on cervical cancer could yield beneficial results.